RIPK2-Mediated Autophagy and Negatively Regulated ROS-NLRP3 Inflammasome Signaling in GMCs Stimulated with High Glucose. (14th August 2019) - Gao, Chenlin; Chen, Jiao; Fan, Fang; Long, Yang; Tang, Shi; Jiang, Chunxia; Wang, Jiying; Xu, Youhua; Xu, Yong
Abstract : Background . Hyperglycemia plays a vital role in diabetic nephropathy (DN); autophagy and its potential upregulator receptor-interacting protein kinase 2 (RIPK2) are associated with ROS, which play a potential role in regulating NLRP3, and may be involved in inflammation in DN. Aim . In this study, we aimed to explore the mechanisms mediated by RIPK2 in autophagy and the relationship with ROS-NLRP3 of DN, by investigating the levels of RIPK2 and autophagy in glomerular mesangial cells (GMCs) stimulated with high glucose. Material and Methods . GMCs were divided into the following groups: normal group (NC), high glucose group (HG), and RIPK2 siRNA group. RIPK2, LC3, caspase1, and IL-1 β levels were measured by western blotting and RT-PCR. Autophagosomes were measured by GFP-RFP-LC3; ROS were detected by DCFH-DA. Results . High glucose upregulated RIPK2 and LC3 in GMCs during short periods (0-12 h) (p < 0.01 ), while RIPK2 and LC3 were significantly downregulated in the long term (12-72 h) (p < 0.01 ); these changes were positively correlated with glucose concentration (p < 0.01 ). In addition, levels of ROS, caspase1, and IL-1 β increased in a time- and dose-dependent manner in the high glucose group, even with an increased expression of LC3 (p < 0.01 ). However, LC3 expression decreased in the siRIPK2 group, while levels of ROS, caspase1, and IL-1 β increased (p < 0.01 ). Conclusions . Autophagy was activated by high glucose at short time periods but was inhibited in the long term, demonstrating a dual role for high glucose in autophagy of GMCs. RIPK2 regulates ROS-NLRP3 inflammasome signaling through autophagy and may be involved in the pathogenesis of DN.